Videogame and Computer Intervention Effects on Older Adults' Mental Rotation Performance - Taylor, Brad (Games Health J, 2021)
Objective: This article examined older adults' performance on two components of a mental rotation task (reaction time and rotation rate) in a home-based intervention study of videogame (Crazy Taxi [CT]) and computerized cognitive training (PositScience InSight). Materials and Methods: Participants were randomized to one of three groups: one group played an off-the-shelf videogame (i.e., CT), the second group engaged in a computerized training program focused on fast perceptual comparisons, visuospatial working memory, rapid scanning of a visual array and pattern recognition, visual discrimination, and selective and divided attention and processing speed (i.e., InSight), and the third (control) group received no training. Training in the two intervention conditions consisted of 60 training sessions of 1 hour each, which were completed in 3 months (5 hours a week). As part of a larger study, participants received mental rotation testing, which was administered immediately before (baseline), after (post-test), and 3 months after (follow-up) training. Results: Although the InSight group showed greater improvements in rotation rate at the immediate post-test, by the 3-month follow-up, the combined treatment groups (CT and InSight) had improved more than controls. Conclusion: The improvements in mental rotation performance found at 3-month follow-up add additional support to previous research, showing visuospatial benefits of both videogame play and cognitive training in older adults. Common elements of both interventions may include expansion of the attentional field of view and faster visual comparison efficiency.